Cyr61 is involved in neutrophil infiltration in joints by inducing IL-8 production by fibroblast-like synoviocytes in rheumatoid arthritis - Zhu, Xianjin (BioMed Central, 2013)
INTRODUCTION: It is well known that neutrophils play very important roles in the development of rheumatoid arthritis (RA) and interleukin (IL)-8 is a critical chemokine in promoting neutrophil migration. We previously showed that increased production of Cyr61 by fibroblast-like synoviocytes (FLS) in RA promotes FLS proliferation and Th17 cell differentiation, thus Cyr61 is a pro-inflammatory factor in RA pathogenesis. In this study, we explored the role of Cyr61 in neutrophil migration to the joints of RA patients. METHODS: RA FLS were treated with Cyr61 and IL-8 expression was analyzed by real-time PCR and ELISA. The migration of neutrophils recruited by the culture supernatants was determined by the use of a chemotaxis assay. Mice with collagen-induced arthritis (CIA) were treated with anti-Cyr61 monoclonal antibodies (mAb), or IgG1 as a control. Arthritis severity was determined by visual examination of the paws and joint destruction was determined by hematoxylin-eosin (H&E) staining. Signal transduction pathways in Cyr61-induced IL-8 production were investigated by real-time PCR, western blotting, confocal microscopy, luciferase reporter assay or chromatin immunoprecipitation (ChIP) assay. RESULTS: We found that Cyr61 induced IL-8 production by RA FLS in an IL-1β and TNF-α independent pathway. Moreover, we identified that Cyr61-induced IL-8-mediated neutrophil migration in vitro. Using a CIA animal model, we found that treatment with anti-Cyr61 mAb led to a reduction in MIP-2 (a counterpart of human IL-8) expression and decrease in neutrophil infiltration, which is consistent with an attenuation of inflammation in vivo. Mechanistically, we showed that Cyr61 induced IL-8 production in FLS via AKT, JNK and ERK1/2-dependent AP-1, C/EBPβ and NF-κB signaling pathways. CONCLUSIONS: Our results here reveal a novel role of Cyr61 in the pathogenesis of RA. It promotes neutrophil infiltration via up-regulation of IL-8 production in FLS. Taken together with our previous work, this study provides further evidence that Cyr61 plays a key role in the vicious cycle formed by the interaction between infiltrating neutrophils, proliferated FLS and activated Th17 cells in the development of RA.